Interactions among Ecological Factors That Explain the Psychosocial Quality of Life of Children with Complex Needs - Sandy Thurston; Louise Paul; Chenglin Ye; Patricia Loney; Gina Browne; Lehana Thabane; Peter Rosenbaum (Hindawi Limited, 2010)
Purpose. To explore the associations and interactions among ecological factors and explain the psychosocial quality of life of children with complex needs. Methods. In this cross-sectional survey consenting parents were identified by the Children's Treatment Network. Families were eligible if the child from 0 to 19 years, resided in Simcoe/York, and there were multiple family needs. Regression analysis was used to explore associations and interactions. n=429. Results. Younger children, without conduct disorder, without hostile and punitive parenting and with low adverse family impact demonstrated the highest levels of psychosocial quality of life. Statistically significant interactions between processes of care and parent variables highlight the complexity of real life situations. Conclusions. It is not possible to fully understand the child's psychosocial quality of life in complex needs families by considering only simple associations between ecological factors. A multitude of factors and interactions between these factors are simultaneously present and the care of these families requires a holistic approach.